STRATEGI PENINGKATAN KARAKTER RELIGIUS SISWA MELALUI PENERAPAN BUDAYA PESANTREN DI MTs NURUL ULUM PUTRI KEBONSARI MALANG - Maulida Hibna Fauza; Dian Mohammad Hakim; Adi Sudrajat (VICRATINA, 2022)
It is the duty of parents to educate their children well. Especially in children's characters. Along with the times, in Indonesia there are many problems of morality and deviations between the results of education and other deviant behavior, especially at the age of teenagers. So it is necessary to revitalize character education.MTs Nurul Ulum is part of a school that does not only study general knowledge but also religious knowledge. Because MTs Nurul Ulum is a pesantren-based school, where the school is under the auspices of the Nurul Ulum Islamic boarding school. From the above background, the researcher formulates the problem of strategy, namely planning, implementation, and evaluation in improving religious character through the application of Islamic boarding school culture. The purpose of this study was to determine how planning, implementation, and evaluation in improving religious character through the application of pesantren culture. The research method used is a case study type approach that collects data in the form of words and pictures with interview, observation, and documentation data collection techniques. While the data analysis technique used is the Miles and Huberman model, namely data condensation, data presentation, and drawing conclusions. From the results of the research that has been done, it can be obtained as 1) Planning to increase the character of students through the application of Islamic boarding school culture, including planning educational programs. , religious activities, and observing the character of students.